Is intrinsic value priced in the cross section of stock returns? - Panayiotis G. Artikis; Christos G. Kampouris (Cogent Economics & Finance, 2022)
This paper provides insights about the information content and predictive ability of the intrinsic value of the firm in an asset pricing context. The intrinsic value of a firm is of great importance for both the management and the investors of the company. We seek to assess whether the value-to-price (V/P) ratio, estimated with the residual income model (RIM), can explain the cross section of stocks returns. The study enhances the literature in the area of asset pricing by developing a new intrinsic value risk factor, which is a zero-investment portfolio that is neutral to the size, book-to-market equity ratio and the momentum effect. Furthermore, we incorporate in the RIM, for the first time, a time-series model that does not rely on analysts' forecasts for the estimation of the key parameters of the model. A unique dataset from Greece, Italy, Spain and Portugal is utilized, from 31/12/2000 to 30/6/2019, that has a number of idiosyncrasies that are not observable in other developed markets, contributing by this way to the necessary accumulation of non-US research. The results show that the new intrinsic value risk factor absorbs the information content of the HML factor and explains better the cross section of returns, mainly for small size and high book to market value companies.
Keywords: 330; Corporate Finance; Investment & Securities; Financial Accounting; Financial Management; Risk Management